Site‐Selective C(sp3)‐H Alkenylation Using Decatungstate Anion as Photocatalyst - Wang, Yi‐Ting; Shih, Yi‐Lun; Wu, Yen‐Ku; Ryu, Ilhyong (Advanced synthesis & catalysis, 2022)
Site‐selective C(sp3)‐H alkenylation was achieved under photo‐irradiation in the presence of a catalytic amount of decatungstate anion, W10O324−. In this reaction, the radical addition/β‐scission sequence is successfully combined with photocatalytic C(sp3)‐H functionalization. The reaction using weaker C−H bonds such as those in THF revealed that the benzenesulfonyl radical itself underwent HAT directly from the C−H bond, and a decatungstate anion participated in a chain‐repairing step.